INTERNATIONAL PERSPECTIVES ON READING ASSESSMENT OF CURRICULUM - BASED ASSESSMENT OF READING INENGLAND AND WALES - Ali, A Rasyid; Adiati, Mrs (Reflective, 2013)
Inetrantional Perspectives on reading Assessment of Curriculum-Based Assesment of Reading in England and Wales. Reading is the core precedence for University student due to their accomplishment in academic life. This the background to the pilot assessment and the basis for assessment that materials for the assessment model and the need for evaluation. Evaluation trials : some findings. Lessons for the future : psychometrics and psychology of teacher assessment. The need for a coherent theory of fluent reading.Keyword : curriculum, reading, asessment